The Role of Media in International Relations – Case study of Hungary and the European Union - Korcsogová, Lucia (2020)
In today´s globalized world, since access to news is mostly secured, media bias has emerged as a real concern. Democratic societies especially rely on unbiased sources of information, since the news provided through mass media affect the public opinion, based on what important political decisions are made. Media theory helps us to understand and effectively analyse how mass media influences our perception of reality. In this thesis, this media influence via online news sites is examined through the case study of the relations between Hungary and the European Union, focusing on the topic of the Sargentini report. The methods chosen for this work are comparative analysis and discourse analysis.